Defiant - Sanderson, Brandon (Sanderson, Brandon, 2023)
Spensa made it out of the Nowhere, but what she saw in the space between the stars has changed her forever. She came face to face with the Delvers, and finally got answers to the questions she's had about her own strange Cytonic gifts. The Superiority didn't stop in it's fight for galactic dominance while she was gone, though. Spensa's team, Skyward Flight, was able to hold Winzik off, and even collect allies to help with the cause, but it's only a matter of time until humanity - and the rest of the galaxy - falls. Defeating them will require all the knowledge Spensa gathered while in the Nowhere. But being Cytonic is more complicated than she ever could have imagined. Now, Spensa must ask herself: how far is she willing to go for victory, if it means losing herself - and her friends - in the process.
Keywords: Spensa : (fiktiivinen hahmo); sodat; selviytyminen; avaruuslennot; lentäjät; alienit; galaksit; tähtienvälinen avaruus